2019
DOI: 10.18182/tjf.482386
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale habitat utilization by birds in an ancient oak (Quercus spp.) wood-pasture in southwestern Turkey

Abstract: Fine-scale habitat utilization by birds in an ancient oak (Quercus spp.) wood-pasture in southwestern Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To preserve the important biological hot spots and structures in wood producing areas, it is crucial to implement an ecosystem-based management approach as well as an appropriate management protocol for these species in protected areas and across the entire forest landscape. Since many beetles are a key food source for woodpeckers and other insectivorous birds, conservation work is also important for the protection of insectivorous birds (Bergner et al, 2015;Kalay Göktepe et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To preserve the important biological hot spots and structures in wood producing areas, it is crucial to implement an ecosystem-based management approach as well as an appropriate management protocol for these species in protected areas and across the entire forest landscape. Since many beetles are a key food source for woodpeckers and other insectivorous birds, conservation work is also important for the protection of insectivorous birds (Bergner et al, 2015;Kalay Göktepe et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Competition among species can influence their distributions and utilization of environmental resources (Han et al, 2019). In previous studius of birds in oak habitats in Türkiye it has been shown that for the number of species a positive effect can be seen from the age of the oaks (Bergner et al, 2015) and the size and density of oaks (Göktepe et al, 2019). For species that rely on the oaks for nesting and foraging, e.g.…”
mentioning
confidence: 99%